Tadalafil in the treatment of erectile dysfunction - Robert M Coward; Culley C Carson (Dove Medical Press, 2008)
Robert M Coward, Culley C CarsonDivision of Urologic Surgery, University of North Carolina, Chapel Hill, NC, USAAbstract: The treatment for erectile dysfunction (ED) was revolutionized with the development of phosphodiesterase type 5 (PDE5) inhibitors. Tadalafil (Cialis®; Eli Lilly and Company, Indianapolis, IN, USA) is the newest and most versatile PDE5 inhibitor in the clinical armamentarium for the treatment of ED. Its most unique characteristic is its long half-life of 17.5 hours, which lends itself to a longer therapeutic window with on-demand dosing and effective steady-state plasma concentrations with once-daily dosing. Clinical trials have proven its safety and efficacy with both dosing strategies for all severities and etiologies of ED, including difficult-to-treat ED. This thorough review will discuss ED, the physiology of penile erection and the role of PDE5, and all aspects of tadalafil, from its development, through its pharmacology, to its latest clinical studies and indications.Keywords: tadalafil, Cialis, PDE5 inhibitors, phosphodiesterase type 5, erectile dysfunction, penile erection